ナンキョク チョウルイ ケツエキ チュウ ノ ニョウソ ケイセイ:ペンギン ケツエキ チュウ ノ チッソ カゴウブツ ト カンゾウ・ジンゾウ チュウ アルギナーゼ ノ リョウ - Rodrigues, Edson; Rosa, Rubens; Bacila, Metry (1998)
P(論文) アデリーペンギン属の, ゼンツーペンギンPygoscelis papua, アゴヒゲペンギンPygoscelis antarctica, アデリーペンギンPygoscelis adeliaeの肝臓・腎臓中のアルギナーゼ量と動力学についての研究を行った。ゼンツーポンギンでは24時間絶食個体に比べて, 給餌個体の血中尿素量は高かった。アゴヒゲペンギンの場合, 給餌個体の血中尿素量は, 絶食個体の1.5倍であった。そして, 給餌したゼンツーペンギンの血中尿素濃度は, 絶食個体の3.5倍であった。また, アゴヒゲペンギン給餌個体の尿酸値は絶食個体の2倍, ゼンツーペンギンは4.8倍であった。肝臓中のアルギナーゼ活性は, アゴヒゲペンギン活性は, アゴヒゲペンギン成体でタンパク質1mg当たり561mU, ゼンツーペンギン成体では208mUであった。肝臓ホモジナイズから得たアルギナーゼのL-アルギニンに対するミカエリス定数KmはpH9.5で16.0±2.0mMであった。一般に鳥類のアルギナーゼは, 100-200mMの高いKm値を示す。高タンパク餌料, 高血中尿素量は, 肝臓アルギナーゼの量とアルギナーゼの基質に対する高い親和性の結果である。 A study was carried out on the levels and the kinetics of liver and kidney arginase from Pygoscelis penguins, the gentoo Pygoscelis papua, the chinstrap, Pygoscelis antarctica, and the Adelie, Pygoscelis adeliae. Higher values of blood urea were found in the gentoo penguins in the native state when compared with specimens maintained in the fasting state for 24 hours. In the chinstrap penguin Pygoscelis antarctica the average value for blood urea was 1.5 times higher in the native state than in the fasting condition. In the native gentoo penguin P. papua the relative increase in the blood urea concentration is as high as 3.5 times in regard to the levels found in the fasting state. In regard to the blood levels of uric acid, the difference between the native state and the fasting state is 2.0 times for P. antarctica and 4.8 times for P. papua. Specific activities of arginase assayed in penguin liver were 561 mU/mg protein and 208mU/mg protein for adult P. antarctica and P. papua respectively. Kinetic studies with arginase from penguin liver homogenates showed Km values for L-arginine of 16.0±2.0mM at pH9.5. Arginase from birds possesses in general high Km values (between 100-200mM). It seems then that the high protein diet and the high levels of blood urea of penguins are a consequence of the levels of hepatic arginase and the high affinity of this enzyme toward its substrate. departmental bulletin paper